Dairy veterinarians' skills in motivational interviewing are linked to client verbal behavior. (19th October 2020) - Svensson, C.; Forsberg, L.; Emanuelson, U.; Reyher, K. K.; Bard, A. M.; Betnér, S.; von Brömssen, C.; Wickström, H.
Abstract : Veterinarians often give advice in a persuasive form, a style that has been shown to evoke resistance to change in clients experiencing psychological ambivalence (i.e. those who see both advantages and disadvantages to changing). With this style of communication, veterinarians run the risk of counteracting their purpose to encourage clients to follow recommendations. Motivational interviewing (MI) is a client-centered communication methodology that aims to facilitate clients' internal motivation to change. In MI, Change Talk represents clients' own statements expressing consideration of, motivation for or commitment to behavior change and has been shown to be strongly correlated with behavior change. Sustain Talk is corresponding statements related to maintaining the status quo . The aim of this exploratory study was to evaluate the potential of MI to facilitate behavior change in veterinary herd health management (VHHM) by investigating the effect of dairy cattle veterinarians' MI skills on client Change and Sustain Talk . We recorded VHHM consultancies on 170 Swedish cattle farms performed by 36 veterinarians, randomly distributed into 2 groups: MI veterinarians ( n = 18) had received 6-month training in MI and control veterinarians ( n = 18) had not received any training. Veterinarians' MI skills were assessed using the Motivational Interviewing Treatment Integrity coding system 4.2.1 and categorized as poor_untrained, poor_trained, near moderate and moderate. Client communication was coded using the Client Language Easy Rating coding system. The effect of MI skills on Change Talk, Sustain Talk and Proportion of Change Talk (Change Talk divided by the sum of Sustain Talk plus Change Talk) was investigated using cross-classified regression models with random intercepts for veterinarian and client (farm). The models also included additional explanatory variables (e.g. type of veterinarian and client's satisfaction with the consultation). The veterinarian's MI skills were associated with the client's Change Talk, but results regarding Sustain Talk or Proportion of Change Talk were inconclusive. Clients of veterinarians reaching the highest (i.e. moderate) MI skills expressed 1.5 times more Change Talk than clients of untrained veterinarians. Clients of general large animal practitioners expressed less Sustain Talk than clients of animal health veterinarians and had higher Proportion of Change Talk. Results indicate that learning to practice MI may be one means to improve adherence to veterinary recommendations and to improve efficiency in VHHM services.